Using activity theory to understand the impact of social networking sites and apps use by Saudi postgraduate students. Issue 6 (26th April 2022) - Alghamdi, Abdulelah A.; Plunkett, Margaret
ABSTRACT: Social networking sites and apps (SNSAs) are being used more frequently across the world and yet the nature of this online environment and associated interactions are not fully understood. With no restrictions for SNSAs use related to specific geographical regions, language, age, gender, educational level, or any other factors, it is important to find a concept to describe and explain the components of this online environment and their relationships. This paper describes the environment of SNSAs use by Saudi postgraduate students from the perspective of second-generation activity theory (AT). The findings supported the theoretical framework of AT as a useful lens in understanding SNSAs use from the perspective of students, particularly in a cultural environment where physical communication has restrictions based on gender. A similar AT model can be drawn for the use of SNSAs, taking the perspective of different groups of academic users. The flexibility of the AT model appears at the level of SNSAs as technical and physical tools, and at the level of users' community, which was managed by the explicit and implicit rules relating to communication. This feature reveals the way in which this extended framework can be used to indicate pertinent features of SNSAs.